Investigation of jatropha seed oil as austempering quenchant for ductile cast iron - Terngu, Akor; Terfa, Gundu David (International Journal of Engineering and Technology, 2014)
Austempering is a multi-step process that includes austenitizing, followed by cooling rapidly enough to avoid the formation of pearlite to a temperature above the martensite start (Ms) and then holding until the desired microstructure is formed. It is an isothermal heat treatment process that, when applied to cast iron, produces components that, in many cases, have properties superior to those process by conventional heat treatment. Salt bath has been recognized as the conventional quenching medium for austempering. This study investigates the suitability of jatropha seed oil as quenching medium for asaustempering ductile cast iron. Test samples were austenitized at 9500C; socked for 1hr; austempered for varying periods of 1, 2, 3, 4 and 5hrs. The result showed significant increase in tensile strength and impact energy apart from achieving an appreciable increase in hardness. It also tally with recommended values of ductile cast iron austempered in salt bath, implying that jatropha oil can be used as hot bath for the austempering of ductile cast iron. Keywords: Ausferrite, Austempering, Austenitized, Matrix So, Cked.